2015
DOI: 10.1057/jit.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

A Paradigmatic Analysis of Digital Application Marketplaces

Abstract: Abstract. This paper offers a paradigmatic analysis of digital application marketplaces for advancing information systems (IS) research on digital platforms and ecosystems. We refer to the notion of digital application marketplace, colloquially called "appstores," as a platform component that offers a venue for exchanging applications between developers and end-users belonging to a single or multiple ecosystems. Such marketplaces exhibit diversity in features and assumptions, and we propose that examining this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(66 citation statements)
references
References 54 publications
(105 reference statements)
1
64
0
1
Order By: Relevance
“…We then show how legislation changes affect the platform ecosystem. Our findings also suggest that the participation in the platform ecosystems, as argued in existing literature [3], [6], is not always prompted to ecosystem health and prosperity motives when the platform adoption is enforced and it is the only choice.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…We then show how legislation changes affect the platform ecosystem. Our findings also suggest that the participation in the platform ecosystems, as argued in existing literature [3], [6], is not always prompted to ecosystem health and prosperity motives when the platform adoption is enforced and it is the only choice.…”
Section: Introductionsupporting
confidence: 69%
“…Gawer & Cusumano [9] studied the strategies for platform leadership building. Paradigmatic analysis of digital application marketplaces and the monopolistic quality of platforms was discussed by Ghazawneh & Henfridsson [6] and Eisenmann et al [10]. The results obtained by Henfridsson & Bygstad [11] on configurational perspectives of digital infrastructures evolution demonstrated the generative mechanisms of such infrastructures.…”
Section: Introductionmentioning
confidence: 99%
“…Anderson et al, 2014;Clemons, 2010;Koh & Fichman, 2014;Rai, Patnayakuni, & Nainika, 2006;Xu & Zhang, 2013). Significantly for our research, some have suggested that the emergent nature of platforms calls for distributed rather than centralised governance arrangements (Ghazawneh & Henfridsson, 2015;Nielsen & Aanestad, 2006;Tiwana, Konsynski, & Bush, 2010). Indeed, the acknowledgement that platforms, and the value of platforms, are co-created by stakeholders (Ceccagnoli et al, 2012;Lusch & Nambisan, 2015) leads to a more general questioning of existing assumptions of platform control in favour of a more distributed governance arrangement (one in which shared visualisation remains important).…”
Section: Platform As Collectively Visualised Organizational Formmentioning
confidence: 81%
“…Reversely, if the platform is too malleable, it easily becomes too fragmented to serve as a platform. Ghazawneh and Henfridsson (2015) proposed a typology of platform-based marketplaces, in terms of openness: closed, censored, focused and open.…”
Section: Lightweight and Heavyweight Itmentioning
confidence: 99%